Oxidative stress protein Oxr1 promotes V‐ATPase holoenzyme disassembly in catalytic activity‐independent manner. (17th December 2021) - Khan, Md. Murad; Lee, Seowon; Couoh‐Cardel, Sergio; Oot, Rebecca A; Kim, Hyunmin; Wilkens, Stephan; Roh, Soung‐Hun
Abstract: The vacuolar ATPase (V‐ATPase) is a rotary motor proton pump that is regulated by an assembly equilibrium between active holoenzyme and autoinhibited V1 ‐ATPase and Vo proton channel subcomplexes. Here, we report cryo‐EM structures of yeast V‐ATPase assembled in vitro from lipid nanodisc reconstituted Vo and mutant V1 . Our analysis identified holoenzymes in three active rotary states, indicating that binding of V1 to Vo provides sufficient free energy to overcome Vo autoinhibition. Moreover, the structures suggest that the unequal spacing of Vo 's proton‐carrying glutamic acid residues serves to alleviate the symmetry mismatch between V1 and Vo motors, a notion that is supported by mutagenesis experiments. We also uncover a structure of free V1 bound to Oxr1, a conserved but poorly characterized factor involved in the oxidative stress response. Biochemical experiments show that Oxr1 inhibits V1 ‐ATPase and causes disassembly of the holoenzyme, suggesting that Oxr1 plays a direct role in V‐ATPase regulation. Synopsis: The mechanism controlling reversible assembly of the conserved proton pump vacuolar ATPase (V‐ATPase) essential for organelle acidification remains unclear. This work combines structural data and biochemical analysis on reconstituted yeast holoenzymes to identify Oxidation resistance protein 1 (Oxr1) as a novel regulator of V‐ATPase function. V‐ATPase assembly from Vo and V1 subcomplexes is independent of ATP hydrolysis. Vo c ‐ring glutamate asymmetry is required for holo V‐ATPase formation and function, as supported by mutational analysis. TLDc domain protein Oxr1 is a conserved V1 ‐ATPase complex component. Oxr1 inhibits V‐ATPase activity and promotes holoenzyme disassembly. Abstract : Comprehensive Cryo‐EM and biochemical analysis identifies Oxr1 as novel binding partner of V‐ATPase, controlling reversible enzyme assembly.